2014
DOI: 10.3892/ol.2014.2046
|View full text |Cite
|
Sign up to set email alerts
|

Association between the low-dose irinotecan regimen-induced occurrence of grade 4 neutropenia and genetic variants of UGT1A1 in patients with gynecological cancers

Abstract: The occurrence of severe neutropenia during treatment with irinotecan (CPT-11) is associated with the *6 and *28 alleles of uridine diphosphate glucuronosyltransferase 1A1 (UGT1A1). However, the correlation between these variants and the occurrence of severe neutropenia in a low-dose CPT-11 regimen for the treatment of gynecological cancers has not been extensively studied. There are also no studies regarding the association between the 421C>A mutation in ATP-binding cassette sub-family G member 2 (ABCG2) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 34 publications
(43 reference statements)
2
8
0
Order By: Relevance
“…Nakaura et al (18) showed that the wildtype UGT1A1*28 accounted for 46% and 76% in the Caucasian and Asian populations, respectively, indicating significant inter-ethnic differences. Etienne-Grimald et al (19) (27). In this study, the homozygous and heterozygous mutations of UGT1A1 showed a predictive effect when the dose of irinotecan was reduced.…”
Section: Discussionsupporting
confidence: 53%
“…Nakaura et al (18) showed that the wildtype UGT1A1*28 accounted for 46% and 76% in the Caucasian and Asian populations, respectively, indicating significant inter-ethnic differences. Etienne-Grimald et al (19) (27). In this study, the homozygous and heterozygous mutations of UGT1A1 showed a predictive effect when the dose of irinotecan was reduced.…”
Section: Discussionsupporting
confidence: 53%
“…In many studies, Caucasians were enrolled and a larger initial dose of irinotecan may have been selected, but the dose of irinotecan was not investigated. Previous studies revealed that UGT1A1*28 and UGT1A1*6 have a predictive effect on the adverse reactions of intermediate or high dose of irinotecan, but not on a low dose of irinotecan [27]. In this study, the homozygous and heterozygous mutations of UGT1A1 showed a predictive effect when the dose of irinotecan was reduced.…”
Section: Discussionsupporting
confidence: 48%
“…Moriya et al . 31 reported that ANC nadir in patients carrying UGT1A1*6/*28 , *6/*6 were significantly lower compared with those with *1/*1 .…”
Section: Discussionmentioning
confidence: 96%
“…This revealed that patients carrying variant of UGT1A1 genotype had a significantly lower ANC nadir in the first and second cycle. Moriya et al 31 reported that ANC nadir in patients carrying UGT1A1*6/*28, *6/*6 were significantly lower compared with those with *1/*1. ABCC2 protein is expressed in liver, kidney, and small intestine, and also plays a primary role in biliary excretion of irinotecan and its metabolites 32,33 .…”
Section: Discussionmentioning
confidence: 99%